2016
DOI: 10.1136/bmjopen-2015-008703
|View full text |Cite
|
Sign up to set email alerts
|

Changes of individual perception in psychosocial stressors related to German reunification in 1989/1990 and cardiovascular risk factors and cardiovascular diseases in a population-based study in East Germany

Abstract: ObjectivesAim was to examine the relationship between individually perceived changes in psychosocial stressors associated with German reunification and cardiovascular effects. We hypothesised that higher levels of psychosocial stress related to German reunification were associated with an increase in cardiovascular risk factors and cardiovascular diseases (CVDs).DesignCross-sectional data from 2 cohort studies in East Germany were used: Cardiovascular Disease, Living and Ageing in Halle Study (CARLA), and Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Another longitudinal German study, KORA (Cooperative Health Research in the Augsburg Region in South Germany), showed a similar prevalence of hypertension (49.2%) at baseline, but a much lower achievement of treatment targets in patients on antihypertensive pharmacotherapy (29.6% in men; 43.9% in women) [ 31 ]. The highest prevalence of hypertension was found in CARLA (the Cardiovascular Disease, Living and Ageing in Halle Study in East Germany) with 66.7% in men and 76.9% in women, which might be due to an overall older study population (mean age in women: 50.0 years; mean age in men: 61.3 years) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal German study, KORA (Cooperative Health Research in the Augsburg Region in South Germany), showed a similar prevalence of hypertension (49.2%) at baseline, but a much lower achievement of treatment targets in patients on antihypertensive pharmacotherapy (29.6% in men; 43.9% in women) [ 31 ]. The highest prevalence of hypertension was found in CARLA (the Cardiovascular Disease, Living and Ageing in Halle Study in East Germany) with 66.7% in men and 76.9% in women, which might be due to an overall older study population (mean age in women: 50.0 years; mean age in men: 61.3 years) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We consider it likely that growing up in a socioeconomically disadvantaged family characterised by parental unemployment and financial hardship amplified the observed adverse metabolic health effects for those affected. We concede that having family-level information on exposure to the economic crisis would help to complete the overall picture,26 and allow us to draw inferences regarding the socioeconomic stratification of the health consequences27 of the macrolevel economic shock in postreunification East Germany. Thus, future research on the long-term metabolic health effects of exposure to an economic crisis should provide a closer examination of the role of family-level socioeconomic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Gallo and colleagues found that chronic stress burden in a major life domain for six months, was associated with prevalent CHD and stroke in a Hispanic population in the United States [39]. In a cohort study of Germans, a greater perceived change in stressors as a result of German reunification (worse financial, occupational and personal situation) was related to greater odds of having a self-reported CVD diagnosis in women [40]. In addition to the two cross-sectional studies, the case-control and case-crossover studies demonstrated greater odds of stressful life events prior to stroke in middle aged populations that included women [41, 42].…”
Section: Cardiovascular Disease Outcomes: Clinical Eventsmentioning
confidence: 99%